Peroral Endoscopic Myotomy for the Treatment of Achalasia in a 10-Year-Old Male Patient - Filser, Jörg; Dick, Anke; Meyer, Thomas; Germer, Christoph-Thomas; von Rahden, Burkard H.A. (European Journal of Pediatric Surgery Reports, 2015)
Peroral endoscopic myotomy (POEM) is a new endoscopic treatment for achalasia with very good short-term results in adults. Data about POEM in pediatric patients are missing. We present the case of a 10-year-old male patient with type I (classic) achalasia, successfully treated with POEM. The procedure was accomplished in a similar fashion to the technique used in adults. Short-term results were fine, with a complete control of dysphagia and absence of reflux. We suggest that POEM is a suitable option in pediatric patients—similar to adults—but long-term results must be awaited.
Keywords: achalasia; POEM; peroral endoscopic myotomy